Guided Paragraph Writing / A First Course in English Composition with Structural Practice - Jupp T. C; Milne John (Heinemann Educational Books, 1988)
This is a first course in English composition with structural practice which leads the foreign learner at an early stage of English from structurally correct simple sentences to the planning and writing of a complete paragraph on straightforward personal subjects. Introduction, The Weekly Holiday, Yesterday Evening, Yourself, The Next Public Holiday, Planning of Subject Matter, An Unhappy First Visit, Unexpected Money, An Unwelcome Meeting, An Interesting Place to Visit, Letter Writing, Your Progress in Paragraph Writing, A Dream, Doing Something Wrong, Your Future, A Difficult Decision in the Past, Being Cheated, Revision and Free Paragraph Writing.